Neonatal endotoxin stimulation is associated with a long-term bronchiolar epithelial expression of innate immune and anti-allergic markers that attenuates the allergic response - García, Luciana Noemí (2020)
Allergic asthma is the most common phenotype of the pathology, having an early-onset in childhood and producing a Th2-driven airways remodeling process that leads to symptoms and pathophysiological changes. The avoidance of aeroallergen exposure in early life has been shown to prevent asthma, but without repeated success and with the underlying preventive mechanisms at the beginning of asthma far to be fully recognized. In the present study, we aimed to evaluate if neonatal LPS-induced boost in epithelial host defenses contribute to prevent OVA-induced asthma in adult mice. To this, we focused on the response of bronchiolar club cells (CC), which are highly specialized in maintaining the epithelial homeostasis in the lung. In these cells, neonatal LPS administration increased the expression of TLR4 and TNFα, as well as the immunodulatory/antiallergic proteins: club cell secretory protein (CCSP) and surfactant protein D (SP-D). LPS also prevented mucous metaplasia of club cells and reduced the epidermal growth factor receptor (EGFR)-dependent mucin overproduction, with mice displaying normal breathing patterns after OVA challenge. Furthermore, the overexpression of the epithelial Th2-related molecule TSLP was blunted, and normal TSLP and IL-4 levels were found in the bronchoalveolar lavage. A lower eosinophilia was detected in LPS-pretreated mice, along with an increase in phagocytes and regulatory cells (CD4+CD25+FOXP3+ and CD4+IL-10+), together with higher levels of IL-12 and TNFα. In conclusion, our study demonstrates stable asthma-preventive epithelial effects promoted by neonatal LPS stimulation, leading to the presence of regulatory cells in the lung. These anti-allergic dynamic mechanisms would be overlaid in the epithelium, favored by an adequate epidemiological environment, during the development of asthma.